Tingkat Pengetahuan Remaja Tentang Kesehatan Reproduksi di SMA Negeri 1 Pekanbaru - Norlita, Wiwik; isnaniar, Isnaniar; Aulia Supriyanti, Siti (As-Shiha: Jurnal Kesehatan, 2022)
The most prominent problems in adolescents related to their growth and development are sexuality, the use of illegal drugs (drugs), and HIV/AIDS orknown as the Adolescent Reproductive Health TRIAD (KRR) problem. Reproductive health is a condition of well-being in all aspects related to the function and role of the reproductive system. Objective: To determine the level of knowledge of adolescents about reproductive health in SMA Negeri 1 Pekanbaru.Research: This type of research is descriptive. This research was conducted on June 3, 2021 - September 09, 2021 at SMA Negeri 1 Pekanbaru. The population in this study amounted to 318 people with the number of samples taken partly from the total population, namely 177 people, the number of research respondents used was 177 respondents. The sampling technique used is the Stratified Random Sampling technique, namely the sampling process technique by dividing the population into strata and then selecting a random sample of each stratum on the population element. The instrument used in this study is a questionnaire in the form of a google form link using the Guttman scale, which is a scale whose answers are firm and consistent, such as yes or no, positive and negative, agree and disagree, true and false answers. Research Results: The level of good knowledge of the score (76-100%) on reproductive health as many as 163 respondents (92.09%). Then students who have a sufficient level of knowledge as many as 13 respondents (7.35%) and a level of knowledge less there is 1 respondent (0.56%). Conclusion: The level of knowledge of adolescents about reproductive health in SMA Negeri 1 Pekanbaru is in the good category of 163 respondents (92.09%).